2022
DOI: 10.3389/fphar.2022.911716
|View full text |Cite
|
Sign up to set email alerts
|

Mitochonic Acid-5 Inhibits Reactive Oxygen Species Production and Improves Human Chondrocyte Survival by Upregulating SIRT3-Mediated, Parkin-dependent Mitophagy

Abstract: Mitochondrial dysfunction is related to the pathogenesis of osteoarthritis (OA); however, there are no effective drugs to treat OA for maintaining mitochondrial homeostasis. Studies have shown that mitochonic acid-5 (MA-5) has a protective effect against mitochondrial damage and plays a role in mitophagy. However, it is not clear whether MA-5 has a beneficial effect on inflammatory articular cartilage. Here, human OA cartilage was obtained from patients undergoing total joint replacement. Interleukin-1β (IL-1β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Therefore, the activation of LC3 II and concomitant decrease in p62 together signify an increase in autophagy. Previous studies have shown that the mitochondria and apoptosis change during the pathogenesis of KOA due to the decrease in autophagy [ 30 ]. In our study, osthole treatment increased the level of LC3 II and decreased the p62 level, which was accompanied by an increase in the number of Aps by TEM in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the activation of LC3 II and concomitant decrease in p62 together signify an increase in autophagy. Previous studies have shown that the mitochondria and apoptosis change during the pathogenesis of KOA due to the decrease in autophagy [ 30 ]. In our study, osthole treatment increased the level of LC3 II and decreased the p62 level, which was accompanied by an increase in the number of Aps by TEM in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The adipokine omentin improves myocardial infarction-induced heart failure by activating mitophagy via the SIRT3/FOXO3 pathway [ 101 ]. Mitochonic acid-5 (MA-5) activates SIRT3 and promotes Parkin-dependent mitophagy in chondrocytes whereas 3-(1H-1,2,3-triazol-4-yl) pyridine (3-TYP), a specific inhibitor of SIRT3, blocks the SIRT3/Parkin pathway [ 107 ]. Thus, SIRT3’s protective actions in several injury models involve mitochondrial quality control by mitophagy.…”
Section: Pathways Of Sirt3 Actionmentioning
confidence: 99%
“…5F), con rming the key role of c-Myc activation on regulating NK KO cell death. Furthermore, when an autophagy-stimulating reagent, mitochonic acid-5 (MA5) or valproic acid (VPA), was added to the PA-treated UCP1 −/− NK cells [31,32] , no obvious restoration in NK cell activities was found, as suggested by cell death, CD69, NKG2D, IFN-γ, and granzyme B (Figs. 5G and H; Supplementary Fig.…”
Section: Similar With Liver Nk Cells From MCDmentioning
confidence: 99%